Dampak Ekonomi Wisata Religi, Studi Kasus Kawasan Wisata Sunan Ampel Surabaya - M. Madyan; Himmatul Kholidah; Dina Fitrisia S; Nisful Laila (Universitas Negeri Surabaya, 2018)
God encourages humans to walk on the Earth or travel (rihlah) in order to extend insights, to see the greatness and Majesty of God and to increase their Faith. This research aims to study how economic impacts of Sharia tourism in the Sunan Ampel Mosque Surabaya to the business activities surrounding that area. The economic impacts of tourism to a certain area consist on direct economic impact, indirect economic impact and induced impact.The research method used descriptive qualitative approach. The data collection was collected by interview and observation process. Informants in this study are people who involve in tourism activities of travellers, traders and labor who work in Sunan Ampel Mosque Surabaya. Analytical techniques are used to reduce, to present, to conclude and to verify the data.The result is the existence of religious tourisms of Sunan Ampel Mosque Surabaya gives the economic impact for the community around. Direct economic impacts increase the income of traders, by 44 percent. The indirect economic impact shown with labors wage of 8,2 percent and induced impact of labor expenses at tourist sites is used the most for food consumptions.